La aplicación del derecho de la eutanasia en el Ecuador - Santana Rodriguez, Geraldine Brigette (2023)
The objective of the research is to make known how the Euthanasia process is carried out in Ecuador as a different alternative means of facing death, from the legal position of people with terminal illnesses (80% advanced) that they decide to have a Dignified Assisted Death in institutions and / or health centers that will be authorized to carry out said procedure; through the application of methods used in Ecuadorian society such as taking personal and graphic surveys, interviews with knowledgeable people such as doctors, lawyers and critics who are responsible for publicizing or discussing the subject. From this, it is sought that Ecuadorian citizens have knowledge about a subject that simply is not so striking, but in depth can generate a change in both life and social in a society that is considered conservative of life..